Constructing policy narratives for transnational mobilization: insights from European citizens’ initiatives - Tosun, Jale; Bulian, Simon (European policy analysis, 2021)
One of the European Union (EU) institutions’ responses to the alleged “democratic deficit” in the EU is the introduction of the European Citizens’ Initiative (ECI). The ECI provides an agenda-setting tool accessible to different advocacy groups. This study investigates the narrative strategies of ECI organizers to mobilize citizens across the EU. Which storytelling characteristics are present in the policy narratives used by ECIs? To address this question theoretically, we rely on the Narrative Policy Framework. Empirically, we examine 59 ECIs registered between 2012 and 2020. The analysis concentrates on three dimensions of policy narratives: the mentioning of (i) story characters and (ii) cost-benefit frames as forms of narrative strategy to increase public attention, and (iii) evidence as a means of persuasion. Our findings show that ECIs predominantly make use of the devil shift in their policy narratives and use cost-benefit frames and evidence to expand the scope of conflict.